An analysis of Bat Hawk Macheiramphus alcinus diet in the Melaky Region of lowland western Madagascar. (2nd January 2016) - Goodman, Steven M; Razakaratrimo, Stéphanie VJ; Roland, Lily-Arison Réné de
Abstract : We present information on the prey taken by the Bat Hawk Macheiramphus alcinus in two different areas of lowland western central Madagascar. These are the first dietary data from Madagascar for this widespread Old World species. The recovered remains were almost exclusively of bats and birds, with a few examples of reptiles and insects. In total, 178 pellets were analysed. On the basis of minimum number of individuals and biomass, bats accounted for 58.3% and 30.3%, respectively, and birds 36.1% and 69.7%, respectively. Amongst the nine species of bats recovered from the pellets, four were represented by multiple individuals, particularly taxa belonging to the families Molossidae and Vespertilionidae that fly in open areas, and for the 11 species of identified birds, all were represented by a single individual. These patterns are interpreted as a specialisation of feeding on bats during a narrow window of time at dusk, as they leave day roost sites, and then using birds in a more general manner to fill in nutritional needs.